Lipase-catalysed preparation of acyl derivatives of the germacranolide cnicin - Monsalve, Leandro Nicolas (2009)
Several acyl derivatives of cnicin were obtained through lipase-catalysed acylation and alcoholysis reactions. In most reactions lipases showed a regioselective behaviour affording only one product. Longer chain acyl derivatives were prepared at lower temperature than the used in lipase-catalysed reactions, to preclude side products formation. The enzymatic approach let to prepare a family of novel acetyl and fatty acid derivatives of cnicin which are not obtainable following traditional organic synthetic procedures.